An Analysis of Junior High School Students' Learning Stress Levels during the COVID-19 Outbreak: Review of Gender Differences - Safena Ningsih; Hengki Yandri; Nuzmi Sasferi; Dosi Juliawati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
The spread of a COVID-19 pandemic has made restlessness, anxiety, stress even depression in society. It also encountered by the students who are undergoing an online learning process, the online learning systems with different learning weights than usual make students depressed and even stressed. Therefore, the purpose of this research is to reveal the level of Junior High School students' stress learning during the COVID-19 pandemic reviewed from gender differences. This research is a comparative quantitative study aimed to compare the difference in learning stress levels of students. This research involved 78 students of State Junior High School 24 Kerinci as respondents. The research data was obtained by using the learning stress scale developed by researchers and analyzed using the Mann-Whitney U test. The results of this study show that there is no difference in learning stress levels among male and female students during the COVID-19 pandemic.